Siapa Yang Diuntungkan dari Revisi UU Desa? Sebuah Refleksi Politik Pemerintahan - Uang, Dedy Pribadi; Situmorang, Alpriyanto (Ministry of Home Affairs, 2025)
The paper discusses the revision of Indonesia’s Village Law, specifically analyzing its socio-political impacts. The study reflects on the extension of the village head’s term and other legislative changes through a political governance lens. The revisions in Law No. 3 of 2024 have sparked controversy, with critics highlighting potential issues such as abuse of power, reduced democratic engagement, and declining public participation. The paper employs a literature review method, conceptually utilizing the six principles of Good Governance—legitimacy, transparency, accountability, rule of law, responsiveness, and effectiveness—as an evaluative framework. The findings indicate that the extension of village heads’ terms, coinciding with the 2024 national elections, serves elite political interests rather than the public good. It has led to concerns about diminished village-level democracy and governance quality. The study concludes that the revised law, while intending to improve governance, mainly benefits political elites, raising doubts about its long-term contribution to village development and democracy.